Why Americans hate the media and how it matters - Ladd, Jonathan M., 1978- (Book collections on Project MUSE., 2012)
As recently as the early 1970s, the news media was one of the most respected institutions in the United States. Yet by the 1990s, this trust had all but evaporated. Why has confidence in the press declined so dramatically over the past 40 years? And has this change shaped the public's political behavior? This book examines waning public trust in the institutional news media within the context of the American political system and looks at how this lack of confidence has altered the ways people acquire political information and form electoral preferences. Jonathan Ladd argues that in the 195.